The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/21514593221138658
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management and Outcomes of Hip Fracture Patients with Advanced Chronic Kidney Disease

Abstract: Aims To explore clinical characteristics, perioperative management and outcomes of Hip Fracture patients with advanced Chronic Kidney Disease (HF-aCKD) compared to the general Hip Fracture population without aCKD (HF-G) within a large volume tertiary hospital in Western Australia. Methods Retrospective chart review of patients admitted with hip fracture (HF) to a single large volume tertiary hospital registered on Australian and New Zealand Hip Fracture Registry (ANZHFR). We compared baseline demographic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Te observation that more severe CKD stage was associated with a higher risk of mortality is in line with most published reports [13,26,28,60,61,[65][66][67][68][69][70][71][72][73][74] on 30-day and 1year mortality; a signifcantly higher LOS in HF patients with CKD was also reported [75]. Some authors, however, observed an increase of all-cause mortality only in patients with CKD stage G4 (but not with stages G3a, G3b, G5, G3-G5) [76] or stage G5 [75,77], in one study of HF patients (>65years of age) no signifcant association was observed between higher stages of impaired renal function and mortality [29], and in another study severity of CKD did not afect 1-year mortality rate and medical complications in patients with intertrochanteric fracture [77].…”
Section: Ckd and Hospital Outcomessupporting
confidence: 89%
“…Te observation that more severe CKD stage was associated with a higher risk of mortality is in line with most published reports [13,26,28,60,61,[65][66][67][68][69][70][71][72][73][74] on 30-day and 1year mortality; a signifcantly higher LOS in HF patients with CKD was also reported [75]. Some authors, however, observed an increase of all-cause mortality only in patients with CKD stage G4 (but not with stages G3a, G3b, G5, G3-G5) [76] or stage G5 [75,77], in one study of HF patients (>65years of age) no signifcant association was observed between higher stages of impaired renal function and mortality [29], and in another study severity of CKD did not afect 1-year mortality rate and medical complications in patients with intertrochanteric fracture [77].…”
Section: Ckd and Hospital Outcomessupporting
confidence: 89%